Coating of pears (Var. ‘Packhams Triumph’) with kafirin protein and its effect on postharvest physiology and shelf-life - Minnaar, Amanda (University of Pretoria, 2013)
Dissertation (MSc(Agric))--University of Pretoria, 2012.